2017
DOI: 10.1017/s1368980016003591
|View full text |Cite
|
Sign up to set email alerts
|

Media audit reveals inappropriate promotion of products under the scope of the International Code of Marketing of Breast-milk Substitutes in South-East Asia

Abstract: Objective: To review regulations and to perform a media audit of promotion of products under the scope of the International Code of Marketing of Breast-milk Substitutes ('the Code') in South-East Asia. Design: We reviewed national regulations relating to the Code and 800 clips of editorial content, 387 advertisements and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 20 publications
6
41
0
1
Order By: Relevance
“…The results of this study are consistent with and advance the knowledge of previous studies related to the Code and the increasing use of breastmilk substitutes worldwide (Baker et al, ; Piwoz & Huffman, ; Vinje et al, ). The types of violations reported by key informants have been described in the literature as damaging to breastfeeding outcomes, namely, interactions with health professionals, cross promotion, and the use of social media channels for product advertisement (Almroth, Arts, Quang, Hoa, & Williams, ; Cheung, ; Coutsoudis, Coovadia, & King, ; Duong et al, ; Liu, Dai, Xie, & Chen, ; Morrow, ; Piwoz & Huffman, ; Pries et al, ; Tang et al, ; Vinje et al, ). The notion of the Code as necessary but insufficient alone is consistent with other studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study are consistent with and advance the knowledge of previous studies related to the Code and the increasing use of breastmilk substitutes worldwide (Baker et al, ; Piwoz & Huffman, ; Vinje et al, ). The types of violations reported by key informants have been described in the literature as damaging to breastfeeding outcomes, namely, interactions with health professionals, cross promotion, and the use of social media channels for product advertisement (Almroth, Arts, Quang, Hoa, & Williams, ; Cheung, ; Coutsoudis, Coovadia, & King, ; Duong et al, ; Liu, Dai, Xie, & Chen, ; Morrow, ; Piwoz & Huffman, ; Pries et al, ; Tang et al, ; Vinje et al, ). The notion of the Code as necessary but insufficient alone is consistent with other studies.…”
Section: Discussionsupporting
confidence: 92%
“…Pries et al, 2016;Tang et al, 2014;Vinje et al, 2017). The notion of the Code as necessary but insufficient alone is consistent with other studies.…”
supporting
confidence: 90%
“…Evidence shows that caregivers in many settings struggle to correctly distinguish between similarly branded BMS products (Berry, Jones, & Iverson, ; Cattaneo et al, ), which can lead to inappropriate feeding. The use of similar branding, pictures, and logos on BMS across a wide age range has been described as detrimental to the effectiveness of national restrictions on BMS advertising (Vinje et al, ). Recommendation 5 of the World Health Organization's Guidance on Ending the Inappropriate Promotion of Foods for Infants and Young Children prohibits any strategies to cross promote foods for infants and young child feeding with BMS (World Health Organization, ).…”
Section: Discussionmentioning
confidence: 99%
“…A scan of mass media across Cambodia, also carried out with Indochina Research, found about 20 min of BMS advertising each day across 10 channels with an average estimated advertising expenditure of US$205,536 (Oslo and Ankershus University College of Applied Siences & Alive & Thrive, ). BMS television advertising was common in Indonesia, Myanmar, Thailand, Cambodia, and Vietnam in 2015–2016 (Vinje et al, ), with numerous products advertised and a high frequency of these advertisements. In Indonesia and Thailand, products for young children 12+ months were observed in advertisements, whereas in Myanmar, Cambodia, and Vietnam, they were for young children 24+ months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation